Like-charge guanidinium pairing from molecular dynamics and ab initio calculations - Vazdar, Mario; Vymětal, Jiři; Heyda, Jan; Vondrášek, Jiři; Jungwirth, Pavel (The journal of physical chemistry. A, 2011)
Pairing of guanidinium moieties in water is explored by molecular dynamics simulations of short arginine-rich peptides and ab initio calculations of a pair of guanidinium ions in water clusters of increasing size. Molecular dynamics simulations show that, in an aqueous environment, the diarginine guanidinium like-charged ion pairing is sterically hindered, whereas in the Arg-Ala-Arg tripeptide, this pairing is significant. This result is supported by the survey of protein structure databases, where it is found that stacked arginine pairs in dipeptide fragments exist solely as being imposed by the protein structure. In contrast, when two arginines are separated by a single amino acid, their guanidinium groups can freely approach each other and they frequently form stacked pairs. Molecular dynamics simulations results are also supported by ab initio calculations, which show stabilization of stacked guanidinium pairs in sufficiently large water clusters.
Keywords: simulace molekulární dynamiky; Water; Guanidine; Molecular Dynamics Simulation; oligopeptidy; Oligopeptides; voda; guanidin